Bisphenol A Exposure Disrupts Enamel Formation via EZH2-Mediated H3K27me3. (July 2021) - Li, H.; Cui, D.; Zheng, L.; Zhou, Y.; Gan, L.; Liu, Y.; Pan, Y.; Zhou, X.; Wan, M.
Enamel formation is a serial and complex biological process, during which related genes are expressed progressively in a spatiotemporal manner. This process is vulnerable to environmental cues, resulting in developmental defects of enamel (DDE). However, how environmental factors are biologically integrated during enamel formation is still poorly understood. Here, we investigated the mechanism of DDE elicited by a model endocrine-disrupting chemical, bisphenol A (BPA), in mouse incisors. We show that BPA exposure leads to DDE in mouse incisors, as well as excessive proliferation in dental epithelial stem/progenitor cells. Western blotting, chromatin immunoprecipitation sequencing, and immunofluorescence staining revealed that this effect was accompanied by upregulation of a repressive mark, H3K27me3, in the labial cervical loop of mouse incisors. Perturbation of H3K27me3 methyltransferase EZH2 repressed the level of H3K27me3 and partially attenuated the excessive proliferation in dental epithelial stem/progenitor cells and DDE induced by BPA exposure. Overall, our results demonstrate the essential role of repressive histone modification H3K27me3 in DDE elicited by exposure to an endocrine-disrupting chemical.